The Aesthetic and Imaginative Dimensions in Receiving Poetic Sayings according to Al-Qurtajani through his Book Minhaj Al-Bulagha and Siraj Al-Udabaa - Al-Arfi, Nassiba (Arts for Linguistic & Literary Studies, 2024)
The research aims to raise the issue of poetic creativity among ancient critics, as it is a language that indicates a functional orientation and involves multiple dimensions supported by the aesthetic and imaginative. Therefore, the discussion will be about the characteristics of aesthetic communication from the point of view of Hazem Al-Qurtajani through his Book Minhaj Al-Bulagha and Siraj Al-Udabaa. The research is divided into an introduction and two sections, the first on the recipient, while the second is on the interaction of the two poles of communication and the realization of the poetic function. The texts will be extrapolated to reach his perceptions and vision on the issue of aesthetic communication. The conclusion showed that poetic meanings are essentially associated with the imaginative element, and that the process of imagination lies in the mental activity carried out by the recipient, which is an interpretive activity in which it reconstructs images. The systematic procedure taken by Al-Qurtajani in rooting the issues of creativity and reception would reveal the depth of imaginative and critical consideration reached by the critical thinking of philosophical critics, and that it should be sensitive to the requirements of the recipient’s conditions, as the issue relates to defining the requirements of literary communication and its objectives.